Teachers’ Perception toward Electronic Student Worksheet Based on chiken manure Waste Treatment Projects to Improve Students' Creative Thinking Skills - Meliana Sri Agustin; Chansyanah Diawati; Tri Jalmo (Jurnal Penelitian Pendidikan IPA, 2023)
The objective of this research was to investigate the Science teachers' perception toward e-worksheet based on chiken manure waste treatment projects to improve students' creative thinking skills. The method used in this research is mixed methods with Sequential Explanatory Design. The data was collected through questionnaire, then analyzed by using descriptive analysis. The questionnaires were distributed to 14 Science teacher respondents and 127 junior high school students in North Metro District. The result shows that teacher have a positive perception toward usage of the electronic students' worksheets based on chiken manure waste treatment projects. The results showed that 79% of teachers had not used project-based e-worksheets; based on students' response questionnaires, 37% of teachers have given project assignments, but the projects were not based on real problems in the environment. Environmental problems that occur in North Metro District is the amount of chicken manure waste issue that causes pollution to the environment around society’s houses. The current worksheets has not completely train students' creative thinking skills and that's skills was in low category. Based on the result It can be concluded that a e-worksheet based on chiken manure waste treatment projects is needed to improve students' creative thinking skills